I'll Root For You and Other Poems - Vendel, Edward van de; Erlbruch, Wolf; Colmer, David, 1960- (Grand Rapids, Michigan : Eerdmans Books for Young Readers, 2018)
"This collection of poems focuses on sports and encouraging young athletes"--|cProvided by publisher.
Keywords: Sports -- Juvenile poetry; Encouragement -- Juvenile poetry; Self-esteem -- Juvenile poetry; Winning and losing -- Juvenile poetry; Sports -- Poetry; Encouragement -- Poetry; Self esteem -- Poetry; Winning and losing -- Poetry; Poetry